Targeted Nanobubbles of PD-L1 mAb Combined with Doxorubicin as a Synergistic Tumor Repressor in Hepatocarcinoma - Chen Y; Luo X; Liu Y; Zou Y; Yang S; Liu C; Zhao Y (International Journal of Nanomedicine, 2022)
Yezi Chen,1,2,* Xiaoqin Luo,2,3,* Yun Liu,4 Yunlei Zou,1,2 Shiqi Yang,1,2 Chaoqi Liu,1,2 Yun Zhao1,2 1Hubei Key Laboratory of Tumor Microenvironment and Immunotherapy, China Three Gorges University, Yichang, People’s Republic of China; 2Medical College of China Three Gorges University, Yichang, People’s Republic of China; 3Department of Medical Imaging Center, Renmin Hospital Affiliated to Hubei University of Medicine, Shiyan, People’s Republic of China; 4Department of Ultrasonography, Yichang Central People’s Hospital, Yichang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun Zhao; Chaoqi Liu, Medical College of China Three Gorges, University, Yichang, People’s Republic of China, Email zhaoyun@ctgu.edu.cn; ctgulcq@163.comPurpose: Ultrasound nanobubbles (NBs) can kill tumor cells, mediated by their effects of cavitation and acoustic perforation through ultrasound, while as novel drug carriers, biomaterial-modified NBs release drugs at a target region. In this work, the ultrasound NBs bridged by biotin-streptavidin were prepared simultaneously to be loaded with both programmed death ligand 1 monoclonal antibody (PD-L1 mAb) and doxorubicin (DOX), which are immune checkpoint inhibitors (ICIs) and chemotherapeutic agents, to synergize immunotherapy and chemotherapy combined with sonodynamic therapy (SDT).Methods: The PD-L1 mAb/DOX NBs, using bridging affinity biotin (BRAB) technology as a bridge, were prepared by thin-film hydration and mechanical oscillation for the targeted delivery of biotinylated PD-L1 mAb and DOX. Characterization and pharmacokinetic studies of PD-L1 mAb/DOX NBs were performed in vitro and in vivo. The antitumor effect of ultrasound-mediated PD-L1 mAb/DOX-NBs was studied in the subcutaneously transplanted tumor of the H22 hepatoma model, and the mechanism of synergistic tumor repression was investigated.Results: The data of in vitro targeting experiments, contrast-enhanced ultrasound imaging (CEUS), in vivo imaging of the small animals imaging system (IVIS), and frozen sections showed that PD-L1 mAb/DOX-NBs have well-targeted aggregation in the tumor. By observing tumor inhibition rate, tissue cell apoptosis, and apoptosis-related gene and protein expression, the PD-L1 mAb/DOX-NBs group showed the best immunotherapy effects, and its tumor volume and mass inhibition rates were about 69.64% and 75.97%, respectively (P < 0.01). Therefore, blocking the PD-1/PD-L1 pathway could improve immune cells’ tumor-killing ability. Antitumor immune cytokines were further enhanced when combined with DOX-induced tumor cell apoptosis and immunogenic cell death (ICD).Conclusion: In summary, ultrasound-mediated PD-L1 mAb/DOX-NBs showed significant synergistic antitumor effects, providing a potential combined immunotherapy strategy for HCC.Keywords: ultrasound targeted nanobubble destruction, tumor immune therapy, immune checkpoint inhibitors, immunogenic cell death, drug delivery